Multimodality imaging based treatment volume definition for recurrent Rhabdomyosarcomas of the head and neck region: An original article - Ferrat Dincoglan; Omer Sager; Selcuk Demiral; Murat Beyzadeoglu (Journal of Surgery and Surgical Research - Peertechz Publications, 2022)
Objective: Rhabdomyosarcomas are among the malignant soft tissue tumors which may originate from primitive mesenchymal cells. These tumors may also be located in the head and neck region and may behave locally aggressive with the invasion of nearby structures. Radiation therapy (RT) may play a role as part of initial management as adjunctive therapy, or for treatment of recurrent disease. Accuracy and precision in RT treatment volume definition have gained utmost importance for achieving optimal treatment results. Herein, we assess multimodality imaging-based RT treatment volume definition for irradiation of recurrent head and neck rhabdomyosarcomas. Materials and methods: Multimodality imaging-based RT treatment volume definition for irradiation of recurrent head and neck rhabdomyosarcomas were evaluated in this study. RT target volume definition by incorporation of magnetic resonance imaging (MRI) or by computed tomography (CT)-simulation images only was assessed with comparative analysis for patients receiving RT for recurrent head and neck rhabdomyosarcomas. Results: As the main outcome of this study, ground truth target volume has been found to be identical to treatment volume definition by CT-MR fusion-based imaging.  Conclusion: Optimal management of recurrent head and neck rhabdomyosarcomas may be improved by precise and accurate RT treatment volume determination. Within this context, the incorporation of MRI in the target and treatment volume definition process may be strongly recommended to achieve improved accuracy and precision in target and treatment volume determination despite the need for further supporting evidence.